Visual tracking of athletes in beach volleyball using a single camera - Mauthner,T.; Koch, C.; Tilp, M.; Bischof, H. (International Journal of Computer Science in Sport, 2007)
This paper aims at successful tracking of beach volleyball athletes during competition using only a single camera. Due to the wide range of possible motions and non-rigid shape changes, the tracking task becomes quite complex. We propose a novel method based on integral histograms, to use a high dimensional model for a particle filter without drastic increase in runtime. We extend integral histograms to handle rotated objects. Additionally to the tracking process, a segmentation of the lower body parts enables generating real world player positions from a single camera view. Comparisons to hand annotated position data revealed sufficient accuracy for classical sport scientific purposes. The paper focuses on beach volleyball but the proposed methods can be utilized in other sports and non sports applications.